Pengaruh Kemiskinan Struktural Terhadap Penegakan Hukum - Lira, M. Adnan (Fakultas Syariah INSURI Ponorogo, 2023)
The relationship between law and structural poverty requires critical thinking which is of course based on an icon that specifically examines the issue of the reciprocal relationship between law and society (people who are classified as poor), that structural poverty (for Indonesian society) seems to have a very strong influence on legal development (law enforcement) in Indonesia, research using normative juridical. The approaches used to conduct this research are: The statutory regulatory approach (the statute approach) and the legal concept analysis approach (analytical & conceptual approach). The influence of structural poverty on law enforcement in Indonesia can be manifested in poverty of knowledge and understanding of legal norms and/or rules so that it can directly or indirectly influence law enforcement in formal and material terms. Apart from that, their ignorance is also a factor that can influence universal law enforcement (which is based on legal development). As a suggestion in this paper, it is hoped that there will be a more constructive understanding of the relationship pattern between law and structural poverty so that looking at the influence of structural poverty on law enforcement does not lead to different perceptions and instead clouds our understanding of law and structural poverty.